The Inclusive Learning in Inclusive Education Provider Schools - Dewi, Wiwi Purnama; Sudadio, Sudadio; Anriani, Nurul (PPSDP International Journal of Education, 2023)
This writing was motivated by the existence of children with special needs who should have equal rights in obtaining education together with students in general at school. Inclusive education held in schools providing inclusive education must properly prepare learning management that is adapted to the conditions of students with special needs. Children with special needs will study together with students in general in regular classes at schools providing inclusive education. Learning that is prepared by taking into account the conditions of students in class and adjustments to other students in regular classes. The author conducted a literature study based on the results of previous research with the topic of inclusive education. The writer said that to organize an inclusive education system, the principle thing that cannot be avoided is to carry out the process of developing components of the education management system in Inclusive Education Provider Schools. They are managerial and curriculum. The managerial includes: planning, implementing and supervising the school system. Inclusive Education Provider Schools must embody the principle of inclusiveness starting from the planning, implementation process, monitoring or supervision, to evaluation and preparation of follow-up plans for the implementation of school programs. And the school curriculum must have expertise in developing and adapting curricula as learning guidelines that are adapted to the needs and individual conditions of their students, including the implementation of special programs.